Níveis de valina digestível em rações com redução de proteína bruta para suínos machos castrados dos 15 aos 30 kg de peso vivo - Lohmann, André Cristiano (2009)
Two experiments were carried out, digestibility and performance growth, to evaluate the levels of digestible valine for barrows from 15 to the 30 kg of body weight. In the digestibility assay were used 20 swines, crossbred, castrated males, with initial weight of 22,88±1,19kg, allotted individually in metabolic cages, in an randomized blocks desing, constituted of five treatments (0,60; 0,67; 0,74; 0,81; 0,88%) and four replicates. In the performance experiment were used 40 swines, barrows, crossbred, with initial weight of 15,49±0,06kg, to evaluate the digestible valine levels, distributed in a randomized blocks design with five treatments (the same), four replicates and two animals per experimental unit. The excretion of N in the urine showed quadratic effect (P<0,05), when using the Broken Line Model (LRP), being observed a reduction until the value of 6,66 g/day of N, corresponding the level of 0,641% of digestible valine in the diet. The retained N: absorbed N ratio showed a quadratic effect (P<0,05), indicating 0,748% as the better digestible valine level. The total excretion of N presented a quadratic effect (P<0,05), in function of the valine levels, being reduced until the level of 0,730% of digestible valine in the diet, and starting from this level the excretion increased again. However daily valine intake (DValI) and valine efficiency utilization for gain (ValEUG) present linear effect (P<0,01). The ValEUG increased in a linear way as the digestible valine levels increased in the diet, indicating reduction in the efficiency of valine use. The LRP model (P<0,01), showed reduction of EUValG up to 0,79% of digestible valine. The creatinina was the only blood parameter the sowed a different (P<0,07). The level of 0,748% of digestible valine was the most appropriate, when being considered the retained nitrogen: absorbed nitrogen, for barrows from 15 to 30 kg of body weight